Edukasi Pengelolaan Obat Rumah Tangga Mencegah Obat Rusak dan Kedaluwarsa Desa Celikah - Nia Azzahra; Devita Devita; Elsa Indriyani; Evi Susanti; Fetrilia Fetrilia; Dia Ayu Lestari; Dina Marlina; Hidayah Dwi Nabila; Intan Nuraini; Intan Permata Sari; Liza Lestari; M Joy Farid Irawan; M Nabil Rahmatullah; Rachel Anastasia (JURNAL PENGABDIAN KADER BANGSA, 2026)
Improper drug storage and disposal practices at the household level remain a public health problem. In Celikah Village, drugs are still found to be stored without regard for temperature, humidity, and expiration dates. This condition has the potential to pose health risks and environmental pollution due to the use of damaged or expired drugs. This community service activity aims to increase community knowledge and awareness regarding the correct management of household drugs based on the principle of Obtain, Use, Store, and Dispose of Drugs Properly (DAGUSIBU). The activity was carried out by students of the Community Service Program (KKN) of Kader Bangsa University, targeting 30 housewives and village health cadres. The implementation method included preparation, coordination with the village government and health workers, preparation of educational materials, and implementation of counseling through lectures, interactive discussions, and distribution of leaflets. Evaluation of the activity was carried out through observation and a question and answer session to assess participants' understanding of the material provided. The activity began with participation in a toddler posyandu (integrated health post) and continued with the delivery of material on how to obtain, use, store, and dispose of drugs safely and rationally. The results of the activity showed that before the education, there were still drug storage habits that did not meet standards. After the activity, participants were able to recognize the signs of damaged and expired medications and understand the importance of proper medication storage. This activity contributed to increasing public awareness as a preventative measure to prevent the use of inappropriate medications.